2016
DOI: 10.4171/jems/612
|View full text |Cite
|
Sign up to set email alerts
|

Metric Diophantine approximation on the middle-third Cantor set

Abstract: Let µ ≥ 2 be a real number and let M(µ) denote the set of real numbers approximable at order at least µ by rational numbers. More than eighty years ago, Jarník and, independently, Besicovitch established that the Hausdorff dimension of M(µ) is equal to 2/µ. We investigate the size of the intersection of M(µ) with Ahlfors regular compact subsets of the interval [0, 1]. In particular, we propose a conjecture for the exact value of the dimension of M(µ) intersected with the middle-third Cantor set and give severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…In the circle T 1 , the analogues of (2.5) and (2.7) were established by Li, Shieh and Xiao [40]. Bugeaud and Durand [4] also recovered these results within the context of Diophantine approximation. Li and Suomala [41] proved the analogue of (2.6) in the torus T d and showed that the assumption dim P F > d − α alone is not enough to guarantee that P(H(F )) > 0.…”
Section: Dimension and Hitting Probabilities Of Random Covering Setsmentioning
confidence: 70%
See 2 more Smart Citations
“…In the circle T 1 , the analogues of (2.5) and (2.7) were established by Li, Shieh and Xiao [40]. Bugeaud and Durand [4] also recovered these results within the context of Diophantine approximation. Li and Suomala [41] proved the analogue of (2.6) in the torus T d and showed that the assumption dim P F > d − α alone is not enough to guarantee that P(H(F )) > 0.…”
Section: Dimension and Hitting Probabilities Of Random Covering Setsmentioning
confidence: 70%
“…A problem suggested by Mahler on how well can points, say, in the middle third Cantor set K be approximated by rational points, has stemmed a number of results [5,6,18,49,57], measuring the sizes of the intersection of K with sets W(ψ) from (1.1) for different values of the approximation speed ψ. These results are in part inconclusive, and lead to conjectures on the size of the set K ∩ W(q −τ ) in [4,39]. In particular, Bugeaud and Durand [4, Conjecture 1] conjectured that…”
Section: Dimension and Hitting Probabilities Of Random Covering Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…#(V (X))−ℓ δ /k . 7 In fact, the exact count for such sequences is known, but we prefer this estimate because it is simpler and yields the same upper bound on the Hausdorff dimension.…”
Section: 2mentioning
confidence: 99%
“…We remark that while in [12], the first-and third-named authors were able to exhibit an optimal Dirichlet function (see Definition 5.2) corresponding to Mahler's second question, it seems that finding an analogous answer to his first question is significantly harder, see e.g. [5,7,12] for detailed discussions and conjectures regarding this question.…”
Section: Introductionmentioning
confidence: 99%